High‐Performance Strain of Lead‐Free Relaxor‐Ferroelectric Piezoceramics by the Morphotropic Phase Boundary Modification. (3rd June 2022) - Li, Tangyuan; Liu, Chang; Shi, Peng; Liu, Xiao; Kang, Ruirui; Long, Changbai; Wu, Ming; Cheng, Shaodong; Mi, Shaobo; Xia, Yuanhua; Li, Linglong; Wang, Dong; et al.
Abstract: Bismuth sodium titanate (BNT)‐based lead‐free piezoceramics are promising for replacing lead‐based piezoceramics in piezoelectric actuators due to their large strains. However, achieving low‐hysteresis large‐strain BNT‐based ceramics over a broad temperature range is challenging, owing to the complexity of the composition design and phase transformation. Herein, a lead‐free relaxor‐ferroelectric (1− x )Bi0.47 Na0.47 Ba0.06 TiO3 ‐ x K0.47 Na0.47 Li0.06 Nb0.99 Sb0.01 O2.99 system (BNBT‐KNLNS) near the morphotropic phase boundary (MPB), achieved by phase‐field simulations and rational composition design (i.e., BNBT with the MPB as the base and the ferroelectric phase of KNLNS as the dopant) is reported. This ceramic exhibits large strains (0.32–0.51%) and low strain hysteresis (11.1–59.9%) over a wide temperature range (25–125 °C), outperforming many state‐of‐the‐art lead‐free piezoceramics. A small fraction of ferroelectric states embedded in the relaxor matrix is experimentally observed, where these states act as seeds, facilitating the reversible relaxor‐to‐ferroelectric transition. In addition, the MPB composition with low energy barriers yields large strain responses, owing to the easy polarization reversal and extension. Consequently, low‐hysteresis large strains are obtained over a broad temperature range. This work provides a novel design route for discovering high‐performance piezoceramics for actuator applications. Abstract : Obtaining low‐hysteresis large‐strain bismuth sodium titanate‐based piezoceramics over a broad temperature range is challenging, owing to the complexity of the composition design and phase transformation. This work demonstrates the relaxor‐ferroelectric piezoceramics of (1− x )Bi0.47 Na0.47 Ba0.06 TiO3 ‐ x K0.47 Na0.47 Li0.06 Nb0.99 Sb0.01 O2.99, achieved by phase‐field simulations and rational composition design. Such system exhibits high‐performance strain, outperforming many state‐of‐the‐art lead‐free piezoceramics.